A Review on Effects of Raw Milk Consumption (International Journal of Innovative Research in Engineering & Management, 2023)
There is still a lot of discussion in the  public about the potential advantages of raw milk intake,  which is becoming more popular. On the one side,  governmental or public health authorities like the Food and  Drug Commission and the Centres for Diseases Prevention  and Prevention are worried about the risk of contracting  milk-borne infections if uncooked milk is tainted with  people germs. This article explains why milk was  pasteurized more than a century ago, how it helped to  decrease the frequency of diseases related with raw milk  intake, and the presence of bacteria in raw milk. Even  when derived from medically normal cows or dairy that  appeared to be of excellent quality, infections were found  in up to a third of all raw milk cases tested. This study  examines some of the widely held claims about raw milk's  health advantages. Raw milk consumption boosts  nutrition, reduces lactose sensitivity, and offers "good"  bacterial has no factual basis and is based on beliefs. There  is some epidemiological evidence suggesting children  growing up in an agricultural environment have a lower  incidence of allergies and asthma; however, a number of  environmental variables may be at play, and raw milk  intake is not directly linked to any ‘‘protective" impact.
Keywords: Lactose Intolerance; Milk; Pathogens; Raw Milk